Integrating Self-Compassion Across the Counselor Education Curriculum. Issue 3 (3rd July 2019) - Coaston, Susannah C.; Lawrence, Christopher
ABSTRACT: Counseling students often struggle with stress, anxiety, self-doubt, and self-criticism. Although counselor education programs encourage self-care, few are able to dedicate a course to tend to student wellbeing. Self-compassion exercises incorporated throughout the curriculum may promote the development of self-kindness, mindfulness, and a sense of common humanity in the face of difficulty or hardship. By creating a classroom environment infused with self-compassion, educators can help prepare students to practice the self-care critical to their ongoing success after graduation. The researchers describe the benefits of self-compassion for counselors-in-training and provides example exercises that can be used in the classroom.